Existence of Mild Solutions for Hilfer Fractional Volterra-Fredholm Integro-Differential Inclusions via almost Sectorial Operators - Bose, C. S. Varun; Udhayakumar, R. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this manuscript, we are mainly investigating the existence of the mild solution for the Hilfer fractional Volterra-Fredholm differential systems via almost sectorial operator. The nonlinear alternative Leray-Schauder fixed point technique for multivalued maps is applied to the fractional calculus concept to demonstrate the conclusions. Finally, an application is provided to demonstrate how the major results might be applied.